Principles of lithography - Levinson, Harry J. (SPIE Press, 2019)
"This text is intended to serve as an introduction to the science of microlithography, but also covers several subjects in depth, making it useful to the experienced lithographer as well. Topics directly related to manufacturing tools are addressed, including overlay, the stages of exposure, tools, and light sources. This updated edition reflects recent advances in technology, including the shift of immersion lithography from development into volume manufacturing, and the movement of EUV lithography from the lab to development pilot lines. New references and homework problems are included. It is expected that the reader of this book will have a foundation in basic physics and chemistry. No topics will require knowledge of mathematics beyond elementary calculus"-- Provided by publisher.
Keywords: Integrated circuits -- Design and construction.; Microlithography.; elektronické knihy; electronic books